SUMUT FASHION WEEK 2023 SEBAGAI RUANG KREATIF DAN DAYA TARIK WISATA DI KOTA MEDAN - Tarigan, Nirwaty (Akademi Pariwisata Darma Agung, 2024)
One of the important assets in developing tourism to improve the city's image and attract tourists is the creativity of the city's people themselves in preserving the city's local culture. In recent years, urban areas have placed an emphasis on innovation to encourage creativity and contribute to the formation of creative spaces. In Indonesia, creative space is increasingly expanding and developing, triggered by social media. This phenomenon attracts people to visit and carry out various creative activities, so that North Sumatra, which has various cultures and ethnicities, feels the need to provide a forum for what has become known as North Sumatra Fashion Week and in 2023, North Sumatra Fashion Week will also be held in November. With this platform, the creative attractiveness of city areas in culture can be better known so that city tourism does not only focus on the physical attractiveness of the city. This research aims to contribute to the available literature by further examining how the creative activities created can form creative spaces in the city of Medan, and what creative activities can be developed as tourist attractions. A qualitative descriptive approach was used in this research, data collection using observation, interviews and literature study. The findings show that various creative activities created in the city of Medan are interpreted collectively by visitors, thus forming a creative space and potentially becoming a tourist attraction in the Medan area. And this research provides explanations and recommendations for stakeholders and further research related to the development of creative spaces and creative tourism in the city of Medan.